Sentir la propia sombra - Ciudad Witzel, Adriana (2023)
Feel Your Own Shadow is a series-in-progress of paintings and watercolors that seeks to bring to light the shadow of the ambivalent condition of motherhood in a world that tends to take it for granted.The title of the series comes from the Guarani people of the Amazon where ‘wisdom’ (Arandu ka ‘aty) means «the one who manages to sense their own shadow».«The darkness embraces everything», says Carlos Papá Mirim Poty, a Guaraní leader. «Mother darkness is where we come from when we are born and where we go when we die. Inside the mother’s womb we have our first existence in darkness [...]».For people like myself, raised in a post-colonial Western paradigm, understanding reality from an indigenous perspective implies a process of unlearning. It involves a monumental effort, perhaps impossible, to transgress the limits of our reason and thus enter a Weltanschauung, a worldview that defies all Western logic and ontology. The act of unlearning has become an arduous but intuitive process for me in which I enter the darkest depths of my being, trusting and letting myself be carried away into new worlds and places, in an attempt «to feel my own shadow».